Structure of a heparan sulphate oligosaccharide that binds to basic fibroblast growth factor. - Habuchi, H (1992)
Binding of basic fibroblast growth factor (bFGF) to the extracellular matrix of cultured bovine aorta smooth muscle cells is likely to be mediated via heparan sulphate, since not only exogenous addition of heparan sulphate to the culture medium but also pretreatment of the cells with heparitinase (but not chondroitinase ABC) resulted in loss of binding. Comparison of the affinity of bFGF to various glycosaminoglycan-conjugated gels showed a direct and specific binding of bFGF to heparan sulphate. Heparan sulphate also bound to a bFGF affinity gel. However, the proportion of heparan sulphate bound varied depending on the source of the HS (more than 90% and 45% with pig aorta heparan sulphate and mouse EHS tumour heparan sulphate respectively). The bound heparan sulphate had the ability to protect bFGF from proteolytic digestion, but the unbound heparan sulphate did not. The results suggest the presence in the bound heparan sulphate of a specific structure involved in binding. Limited digestion with heparitinase I of porcine aorta heparan sulphate yielded 13% oligosaccharides bound to the gel, of which the smallest were octasaccharides. Analysis of a hexadecasaccharide fraction which was obtained at the highest yield among the bound oligosaccharides was performed by h.p.l.c. of the deamination products obtained with nitrous acid and the unsaturated disaccharide products formed by heparitinase digestion. Comparison of the disaccharide unit compositions exhibited a marked difference in IdoA(2SO4)GlcNSO3 and IdoA(2SO4)GlcNSO3(6SO4) units between the bound and unbound hexadecasaccharides. The amounts measured were 3 mol and 1 mol per mol of the former and 0.4 mol and 0.6 mol per mol of the latter. It is likely that the binding of bFGF to heparan sulphate may require the domain structure of the heparan sulphate to be composed of clustering IdoA(2SO4)-GlcNSO3 units.